Anne Guo: capstone - Guo, Anne, artist (Colorado State University. Libraries, 2023)
The artist's statement: When working with fiber techniques, I focus on the concept of style and clothing. I have learned that standard clothing only fits right on some body types. I have a love for Asian fashion, but the sizes are almost way too small for regular American bodies. Finding clothing in the color you want can also be frustrating. So, I show people that fashion does not need to be dictated by the clothing companies. So, each piece of clothing I make is a style I like made with yarn. Embracing the yarn material, I work in crochet, embroidery, and weaving. The idea of clothing that I want to make dictates what process I use. Sometimes, clothing just needs embellishments to level up the piece. When I want to experiment with fluidity in shape in clothing, I go to crochet. I tend to go to weaving's pattern consistency when thinking about patterns. When doing images on clothing, I tend to gravitate to embroidery. It shows that each piece is one of a kind.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers